2023
DOI: 10.1007/s10238-023-01033-0
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a-3p as a potential novel therapeutic by targeting MBD2 to mediate Th17 differentiation in Th17 predominant neutrophilic severe asthma

Abstract: Th17 (T-helper 17) cells subtype of non-T2 (non-type 2) asthma is related to neutrophilic infiltration and resistance to inhaled corticosteroids (ICS), so is also known as severe asthma. Methyl-CpG binding domain protein 2 (MBD2) regulates the differentiation of the Th17 cells, tending to show a therapeutic target in severe asthma. miR-146a-3p is associated with anti-inflammatory characteristics and immunity. Moreover, bioinformatic analysis showed that MBD2 may be a target gene of miR-146a-3p. However, the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The above relationships were simultaneously confirmed in mouse lung tissue. Inhalation of the mimic equivalent of miRNA-146a-3p results in a decrease in MBD2 and the number of Th17 lymphocytes involved in the inflammatory process, inhibition of mucus production, and airway hyperreactivity [67]. In the group of 68 pediatric patients with asthma, the reduction of miRNA-135b and the relationship of this molecule with the increase in CXCL12 (C-X-C motif chemokine ligand 12) were confirmed.…”
Section: Mirnas and Pathways Responsible For The Development Of Asthm...mentioning
confidence: 83%
“…The above relationships were simultaneously confirmed in mouse lung tissue. Inhalation of the mimic equivalent of miRNA-146a-3p results in a decrease in MBD2 and the number of Th17 lymphocytes involved in the inflammatory process, inhibition of mucus production, and airway hyperreactivity [67]. In the group of 68 pediatric patients with asthma, the reduction of miRNA-135b and the relationship of this molecule with the increase in CXCL12 (C-X-C motif chemokine ligand 12) were confirmed.…”
Section: Mirnas and Pathways Responsible For The Development Of Asthm...mentioning
confidence: 83%
“…Two miRNAs, miR-146a-3p and miR-136-3p, both downregulated in serum and tissue were identi ed. Recent research suggested that miR-146a-3p is related to the occurrence and progression of disease including asthma, allergic rhinitis and Paget's disease (Duan et al 2023, Xia et al 2023, Stephens et al 2020). Similarly, miR-136-3p is also reported to inhibit tumorigenesis (Xu 2020).…”
Section: Discussionmentioning
confidence: 99%
“…DHT and E2 (Apex BIO) were first dissolved with 2mL of DMSO (Sigma Aldrich) first and then diluted with corn oil to a final concentration of 2mg/mL in accordance with the manufacturer's protocol. The dosage of DHT and/or E2 (30mg/kg) was adopted in accordance to previous reports with minor modification 14 , 21 . On day 21, mice were anesthetized with intraperitoneal injection of 10% chloral hydrate and northen euthanized with cervical dislocation maneuver.…”
Section: Methodsmentioning
confidence: 99%